Optimized MaxEnt model predicts potential suitable habitats of Bidens bipinnata in China under climate change scenario - Liu, Yi; Chen, Shimao; Zhang, Hong; Luo, Han; Hu, Jiangmiao; Liu, Shoujin (Frontiers in Plant Science, 2025)
Bidens bipinnata, a traditional Chinese medicinal herb, faces threats from overharvesting and climate change. This study integrated species occurrence data with environmental variables (bioclimatic, soil, and topographic factors). Key variables were selected through correlation analysis and contribution assessment for MaxEnt modeling. The model was optimized by tuning feature combinations and regularization multipliers to achieve high predictive accuracy (AUC > 0.9). The optimized model simulated the potential distribution of suitable habitats under current climate conditions and future scenarios (2030s, 2050s, 2070s, 2090s) for SSP1-2.6 and SSP5-8.5. Changes in suitable area, spatial patterns, and centroid migration were analyzed. The Jackknife test identified July precipitation (prec_07) and February mean temperature (tavg_02) as the dominant factors influencing distribution. Under current conditions, the total suitable area is approximately 1.96 million km2, primarily located in central, eastern, and southwestern China. Future projections indicate an overall expansion of suitable habitats, with a trend towards higher latitudes. The distribution centroid, currently in Hubei Province, fluctuates within Hubei under future scenarios, with a more pronounced shift under SSP5-8.5. This study elucidates the ecological drivers and future distribution dynamics of B. bipinnata, providing a scientific basis for its resource conservation, cultivation, and sustainable utilization.